The Political Economy Of The Differential Regional Effects Of Monetary Policy: Evidence From China. (17th March 2021) - Liao, Changjun; Wang, Shengquan
Abstract : Previous studies have argued that heterogeneities across regions in economic and/or financial variables drive the differential regional effects of monetary policy. In this study, we conduct a political economy analysis of the regional effects of China's monetary policy (i.e., economic competition between local governments) as Chinese‐style fiscal decentralization and China's promotion tournament for officials produce regional effects. Furthermore, we use a threshold model and provincial‐level data from 2005 to 2018 to test our hypotheses and estimate exogenous monetary policy shocks. We find that (1) economic competition between regions is a key driver of the asymmetric regional effects of monetary policy and (2) the fiercer the competition a province faces, the less effective the monetary policy is in shaping economic growth there. Our conclusion remains unchanged when we change the threshold variable and divide the sample into three subregions.